Inclusión/Exclusión Dos caras de la sociedad del Antiguo Régimen - CARZOLIO, María Inés coord. (PHOHISTORIA, 2003)
Contiene otros autores: BEZIAN DE BUSQUETS, Enriqueta; GONZALEZ, María Luz; CASALI DE BABOT, Judith; SALVATIERRA, Guillermo; BIANCHI, Diana; PERUCHENA, Lourdes; CASELLI, Elisa; NIEMAN, Raquel